A ideologia nos discursos do Papa Francisco : uma análise sociocognitivo-carismática - Fernandes, Victor Vago (2017)
The main objective of this Master’s thesis is to unveil the ideology in the speeches of Pope Francis. The corpus of our research is formed by 178 homilies uttered by the Pope in the first three years of his pontificate. Provided that the homilies are a peculiar discursive genre, understood as discourses, they were fundamental in the choice of our theoretical-methodological framework. For that matter, we chose Critical Discourse Analysis (CDA) due to its interdisciplinary character, not restraining a single methodology for conducting research, as well as by its explicit positioning in relation to social problems. Among the various approaches that constitute the CDA, we bound our study based on the van Dijk’s sociocognitive enterprise (1999, 2010, 2012, 2014), for it brings us issues related to social power, abuse of power and counterpower, and concerns about the ways in which texts (re) produce and transmit ideologies contrary to social minorities. In addition, this enterprise enables us to understand the relationship between society, cognition and discourse. We also draw upon Weber's contributions (1981, 1999a, 1999b) as of the characteristics of the charismatic leader and Coleman's (2009) charismatic principles. In order to carry out our analysis we delimited sociocognitive categories of van Dijk along with the five characteristics of the charismatic leader of the sociologist Weber and with the three charismatic principles of the anthropologist Coleman. This delimitation allowed us to constitute a table of the categories selected for the conduction of the analyses. The results reveal that the lexical choices of the Holy Father’s discourses are related to the three subjects of great relevance of his government. In his discourses the metaphors are able to convey the ideology of his institution and the polarizations are effective strategies for maintaining the ideology of the Catholic Church. The charisma of the Latin American Supreme Pontiff is the most planned means of the 2013 Conclave of rescueing the tainted image of the Church and the infallible guarantee of restoring the hegemonic power of this twothousand-year institution.